Gelidioid algae a brief resume of the pertinent literature - Santelices, Bernabe (Honolulu, Hawaii University of Hawaii, 1975)
Distributed as a working paper for the use of the Marine Agronomy Program of the University of Hawaii, Department of Botany, under NOAA Contract No. RA/02 with the Office of the United States Department of the Interior, October 1974
Keywords: Algae